2018
DOI: 10.1002/rhc3.12155
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Response After Extreme Events in Taiwan: The Influence of Formal Institutions on Inter‐Organizational Interaction

Abstract: The performance of a disaster response system is related to its capacity to facilitate interaction and situational awareness among the organizations that respond to a disaster event. In line with the assumption that formal institutions have an impact on the organization and performance of a country's disaster management system, governments around the world have sought to improve their disaster management capacities through the promulgation of laws and regulations. The literature, however, is limited in its abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Wang (19) indicated that legal institutions and information communication technology affected the formation and evolution of inter-organizational interactions in Taiwan's disaster reaction system after Chi Chi's earthquake and Morakot's storm. They concluded that situations not only helped the institutional development and disaster but also proposed a management theory and provide policymakers with the insight into how to improve capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Wang (19) indicated that legal institutions and information communication technology affected the formation and evolution of inter-organizational interactions in Taiwan's disaster reaction system after Chi Chi's earthquake and Morakot's storm. They concluded that situations not only helped the institutional development and disaster but also proposed a management theory and provide policymakers with the insight into how to improve capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, Taiwan's disaster management system has evolved as it was challenged by multiple extreme events. Several studies described and analyzed the design and evolution of the institutional structure of Taiwan's emergency management system (See Chen et al, 2006;Hsiung et al, 2010;Tso & McEntire, 2011;Wang, 2018).…”
Section: Methods Data and Analysismentioning
confidence: 99%
“…For instance, Jung et al (2019) emphasize that collaboration risks generated by the 2012 Korean typhoons may have encouraged organizations to establish collaborative ties with other organizations that possess critical resources and information, to increase resource mobilization. In a review of the recovery phases in the interorganizational disaster management field, Wang (2019) sought to reveal how formal institutions influence interorganizational interaction in two Taiwanese disaster management systems. This article reveals that formal institutions have both positive and negative effects on interorganizational interaction in disaster management contexts.…”
Section: Cross-sector Networkmentioning
confidence: 99%